Image Steganography Analysis Using GOST Algorithm and PRNG Based on LSB - Ilham Firman Ashari; Andhika Wibawa Bhagaskara; Jaya Megelar Cakrawarty; Perdana Raga Winata (LPPM Universitas Dian Nuswantoro, 2022)
Security in communication is very important for everyone to pay attention to. To prevent data leakage and illegal retrieval of data, cryptography and steganography can be used. In this study, GOST and XOR LSB with PRNG were used to inject text into images. The final result shows that the combination of these two methods is quite good in terms of image quality, message capacity, embedding speed, and imperceptibility (cannot be seen with the naked eye). Of the 9 image formats tested, 7 images containing messages could be extracted properly with a median MSE of 0.0001935 and a median of PSNR of 85.261. Then, in terms of rotation, all im-age rotations from 90°, 180°, and 270° fail to extract messages and in terms of resizing all sizes from 10%, 30%, 50%, and 80% also fail to extract messages. The average time required for encryption with test data 6 test data is 0.073 seconds with the GOST algorithm, using GOST + XOR LSB with PNRG is 0.485 seconds. By using the XOR combination method LSB with PRNG can store an average of 43.3 bits. From the impercibility test using 5 respondents and visualization using an RGB histogram, it can be seen that there is no difference be-tween the cover image and the stego image.